Inhibition of the cGAS-STING Pathway Attenuates Lung Ischemia/Reperfusion Injury via Regulating Endoplasmic Reticulum Stress in Alveolar Epithelial Type II Cells of Rats - Huang R; Shi Q; Zhang S; Lin H; Han C; Qian X; Huang Y; Ren X; Sun J; Feng N; Xia C; Shi M (Dove Medical Press, 2022)
Renhui Huang,1,2,* Qi Shi,1,* Shutian Zhang,1,2 Hong Lin,1,2 Chengzhi Han,1,2 Xinyi Qian,1 Yijun Huang,1 Xiaorong Ren,1 Jiayuan Sun,3 Nana Feng,4 Chunmei Xia,1 Meng Shi5 1Department of Physiology and Pathophysiology, School of Basic Medical Sciences, Fudan University, Shanghai, 200032, People's Republic of China; 2Department of Clinical Medicine, Shanghai Medical College, Fudan University, Shanghai, 200032, People's Republic of China; 3Department of Respiratory Endoscopy, Department of Respiratory and Critical Care Medicine, Shanghai Chest Hospital, Shanghai Jiao Tong University, Shanghai, 200030, People's Republic of China; 4Department of Respiratory and Critical Medicine, Shanghai Eighth People's Hospital Affiliated to Jiangsu University, Shanghai, People's Republic of China; 5Department of Thoracic and Cardiovascular Surgery, Huashan Hospital, Affiliated with Fudan University, Shanghai, 200040, People's Republic of China*These authors contributed equally to this workCorrespondence: Meng Shi, Department of Thoracic and Cardiovascular Surgery, Huashan Hospital, Affiliated with Fudan University, 12 Wulumuqi Middle Road, Shanghai, 200040, People's Republic of China, Tel +86 15921527577, Email huashan_heart@sina.cn Chunmei Xia, Department of Physiology and Pathophysiology, School of Basic Medical Sciences, Fudan University, Shanghai, 200032, People's Republic of China, Tel +86 13917406439, Email cmxia@fudan.edu.cnPurpose: Endoplasmic reticulum stress (ERS) plays an important role in the pathogenesis of lung ischemia/reperfusion (I/R) injury. Cyclic GMP-AMP synthase (cGAS) is a cytosol dsDNA sensor, coupling with downstream stimulator of interferon genes (STING) located in the ER, which involves innate immune responses. The aim of our present study was to investigate the effects of cGAS on lung I/R injury via regulating ERS.Methods: We used Sprague-Dawley rats to make the lung I/R model by performing left hilum occlusion-reperfusion surgery. cGAS-specific inhibitor RU.521, STING agonist SR-717, and 4-phenylbutyric acid (4-PBA), the ERS inhibitor, were intraperitoneally administered in rats. Double immunofluorescent staining was applied to detect the colocalization of cGAS or BiP, an ERS protein, with alveolar epithelial type II cells (AECIIs) marker. We used transmission electron microscopy to examine the ultrastructure of ER and mitochondria. Apoptosis and oxidative stress in the lungs were assessed, respectively. The profiles of pulmonary edema and lung tissue injury were evaluated. And the pulmonary ventilation function was measured using a spirometer system.Results: In lung I/R rats, the cGAS-STING pathway was upregulated, which implied they were activated. After cGAS-STING pathway was inhibited or activated in lung I/R rats, the ERS was alleviated after cGAS was inhibited, while when STING was activated after lung I/R, ERS was aggravated in the AECIIs, these results suggested that cGAS-STING pathway might trigger ERS responses. Furthermore, activation of cGAS-STING pathway induced increased apoptosis, inflammation, and oxidative stress via regulating ERS and therefore resulted in pulmonary edema and pathological injury in the lungs of I/R rats. Inhibition of cGAS-STING pathway attenuated ERS, therefore attenuated lung injury and promoted pulmonary ventilation function in I/R rats.Conclusion: Inhibition of the cGAS-STING pathway attenuates lung ischemia/reperfusion injury via alleviating endoplasmic reticulum stress in alveolar epithelial type II cells of rats.Graphical Abstract: Keywords: cGAS-STING, endoplasmic reticulum stress, alveolar epithelial type II cells, lung ischemia/reperfusion injury